NAMES OF PLANTS USED IN UZBEK FOLK MEDICINE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article examines the names of medicinal plants used in Uzbek folk medicine, focusing on their formation, lexical-semantic features, and linguocultural significance. The study highlights the relationship between plant nomenclature, folk worldview, practical experience, and perception of nature. Particular attention is paid to nomination principles, synonymy and variation, as well as the distinction between common and dialectal plant names. The process of terminologization of folk plant names and their interaction with modern medicine and pharmacology are also analyzed. The findings demonstrate that medicinal plant names in Uzbek folk medicine function not only as linguistic units but also as essential elements of cultural heritage.